Anti-TNF-α agents Modulate SARS-CoV-2 Receptors and Increase the Risk of Infection Through Notch-1 Signaling - Keewan, Esra’a; Beg, Shazia; Naser, Saleh A. (Frontiers in Immunology, 2021)
Although millions of patients with underlying conditions including rheumatoid arthritis (RA) and Crohn’s disease (CD) are treated primarily with anti-TNF-α agents, little is known about the safety of this standard therapy in possible susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during Coronavirus disease 2019 (COVID-19) pandemic. In this study, we investigated the effect of anti-TNF-α monoclonal antibodies therapy on the cellular entry mechanism of SARS-CoV-2 and increasing the risk of COVID-19 development. We focused on expression and dysregulation of angiotensin-converting enzyme II (ACE2), type II transmembrane serine proteases (TMPRSS2)/ TNF-α converting enzyme (TACE) ratio. We also investigated the mechanism involved in Notch-1 signaling and downstream influence on IL-6, myeloid cell leukemia sequence-1(MCL-1), and intracellular infection by Mycobacterium avium subspecies paratuberculosis (MAP, a possible culprit in autoimmune disease) in macrophages treated with anti-TNF-α drugs. Surprisingly, anti-TNF-α downregulated ACE2 expression by 0.46-fold and increased TMPRSS2/TACE ratio by 44% in THP-1 macrophages. Treatment of macrophages with rIL-6 also downregulated ACE2 and increased TMPRSS2/TACE ratio by 54%. Interestingly, anti-TNF-α treatment upregulated Notch-1, IL-6, and MCL-1 by 1.3, 1.2, and 1.9-fold, respectively, and increased viability and burden of MAP infection in macrophages. Blocking Notch signaling by a γ-secretase inhibitor (DAPT) doubled ACE2 expression, decreased TMPRSS2/TACE ratio by 38%, and decreased MAP viability by 56%. In small group of patients, ACE2 level was significantly lower in the plasma from RA patients on anti-TNF-α treatment compared to healthy control. The data in this important study demonstrated that through Notch-1/IL-6 signaling, anti-TNF-α monoclonal antibodies treatment in THP-1 macrophages and RA patients decreased ACE2 expression and shedding through TMPRSS2/TACE modulation; high circulating ACE2 level is protective against viral infection. More follow up studies are needed to validate the safety of anti-TNF-α therapy in high-risk populations during the COVID-19 Pandemic. A larger clinical study is needed to investigate the plasma level of ACE2 in patients on different treatment options.